Community engagement in youth justice program design. Issue 3 (September 2020) - Butcher, Luke; Day, Andrew; Kidd, Garry; Miles, Debra; Stanton, Steven
Aboriginal young people from rural areas in Australia are significantly over-represented in the youth justice system, and yet there is little evidence to indicate that current programs are having measurable success on rates of re-offending, suggesting alternative approaches are required. Drawing on new directions in human service policy that emphasise the importance of involving community in program design, this study reports the findings of a consultation with Aboriginal community members from one rural community to identify how the ecological validity of youth justice programs may be increased to be more responsive to local need. Eighteen Aboriginal community members from a town in Western New South Wales participated in semi-structured interviews, guided by a culturally informed research methodology. Qualitative content analysis was used to identify key themes that the community saw as important in program design, highlighting the need for consistent levels of support for local and community-driven solutions. Proposed conditions to enhance the ecological validity of programs are discussed.